ANALYSIS OF THE AUDITOR'S EXPERIENCE IN THE USE OF INDEPENDENT EVIDENCE IN AUDIT JUDGMENT IN A PUBLIC ACCOUNTING OFFICE IN THE EAST JAKARTA AREA - Vitho Nuari; Apry Linda Diana; M Yusuf (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2024)
Research This aim for know influence auditor's experience of use audit evidence is not relevant in audit judgment at the KAP in the East Jakarta Region which is registered with the Authority Service Finance (OJK) and the Ministry of Finance (Ministry of Finance) and status active until with period November 2022. Type method research used is method study descriptive with approach study qualitative. Informants on research This taken directly by researchers from the Accounting Firm Public in the East Jakarta Region registered with the Authority Service Finance (OJK) and the Ministry of Finance (Ministry of Finance) and status active until with period November 2022 with amount Informant as many as 30 auditors. Informants on research This determined with Stratified Random Sampling method and obtained as many as 7 KAP with amount Informant as many as 30 auditors, 15 of them have experience not enough of 5 years and 15 others have experience more from 5 years. Source of data used is primary. Result of study prove that variable experience the auditor has influence to use audit evidence is not relevant and audit judgment at the Accounting Firm Public registered with the Authority Service Finance (OJK) and the Ministry of Finance (Ministry of Finance) with status active until with period November 2022.